A multimodal approach identifies lactate as a central feature of right ventricular failure that is detectable in human plasma - Hemnes, Anna; Fortune, Niki; Simon, Katie; Trenary, Irina A.; Shay, Sheila; Austin, Eric; Young, Jamey D.; Britain, Evan; West, James; Talati, Megha (Frontiers in Medicine, 2024)
Background: In PAH metabolic abnormalities in multiple pathways are well-recognized features of right ventricular dysfunction, however, prior work has focused mainly on the use of a single "omic" modality to describe a single deranged pathway. We integrated metabolomic and epigenomic data using transcriptomics in failing and non-failing RVs from a rodent model to provide novel mechanistic insight and translated these findings to accessible human specimens by correlation with plasma from PAH patients. Methods: Study was conducted in a doxycycline-inducible BMPR2 mutant mouse model of RV failure. Plasma was collected from controls and PAH patients. Transcriptomic and metabolomic analyses were done on mouse RV tissue and human plasma. For mouse RV, we layered metabolomic and transcriptomic data for multiple metabolic pathways and compared our findings with metabolomic and transcriptomic data obtained for human plasma. We confirmed our key findings in cultured cardiomyocyte cells with BMPR2 mutation. Results: In failing mouse RVs, 1] in the glycolysis pathway, glucose is converted to lactate via aerobic glycolysis, but may also be utilized for glycogen, fatty acid, and nucleic acid synthesis, 2] in the fatty acid pathway, FAs are accumulated in the cytoplasm because the transfer of FAs to mitochondria is reduced, however, the ß-oxidation pathway is likely to be functional. 3] the TCA cycle is altered at multiple checkpoints and accumulates citrate, and the glutaminolysis pathway is not activated. In PAH patients, plasma metabolic and transcriptomic data indicated that unlike in the failing BMPR2 mutant RV, expression of genes and metabolites measured for the glycolysis pathway, FA pathway, TCA cycle, and glutaminolysis pathway were increased. Lactate was the only metabolite that was increased both in RV and circulation. We confirmed using a stable isotope of lactate that cultured cardiomyocytes with mutant BMPR2 show a modest increase in endogenous lactate, suggesting a possibility of an increase in lactate production by cardiomyocytes in failing BMPR2 mutant RV. Conclusion: In the failing RV with mutant BMPR2, lactate is produced by RV cardiomyocytes and may be secreted out, thereby increasing lactate in circulation. Lactate can potentially serve as a marker of RV dysfunction in PAH, which warrants investigation.